THE IMPORTANCE OF ACCOUNTING IN AGRICULTURAL PRODUCTION UNDER THE CONDITIONS OF THE DIGITAL ECONOMY (American Journal of Business Management, Economics and Banking, 2026)
This article investigates the significance of accounting in agricultural production within the context of the digital economy. Emphasizing transparency, accuracy, and data-driven decision-making, the study analyses how digital transformation reshapes the role of accounting, streamlines management processes, improves resource allocation, and contributes to the sustainability and competitiveness of agricultural enterprises. Modern tools, digital platforms, and the integration of information technologies in accounting processes are examined, along with the emerging challenges and prospects for the development of agricultural accounting. The article concludes by outlining future directions for research and practical application in achieving efficient and sustainable agricultural production.